ANALISIS PENILAIAN PEMBELAJARAN BAHASA INDONESIA KELAS VII SMP NEGERI 17 PONTIANAK - Keti Keti; Abdussamad Abdussamad; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe background of this research is the importance of learning assessment in the learning process because during the current pandemic, the interaction between teachers and students is limited as a result, the learning assessment is not optimal so that the assessment can only be carried out on two aspects, namely knowledge and skills. The purpose of this study was to describe the assessment of aspects of knowledge and skills carried out by Indonesian language teachers for class VII SMP Negeri 17 Pontianak. This study used descriptive qualitative method. The data in this study were sourced from Indonesian language teachers in class VII SMP Negeri 17 Pontianak and students in class VII. . Based on the results of the analysis on the learning assessment, it can be seen that the assessment used by the teacher is not appropriate to be able to evaluate the learning outcomes of students during the online learning period because the questions given by the teacher can result in plagiarism so that students' answers are the same. The similarity is suspected that students get from the same source, it can also be collaborative assessments carried out by teachers on aspects of knowledge and skills that are not fixed so that teachers must pay more attention to assessment strategies.Keywords: Learning Assessment, Knowledge Aspect, And Skill Aspect